Electrical properties of ternary system Bi0.5(Na0.80K0.20)0.5TiO3-0.005LiNbO3-BaTiO3lead-free piezoelectric ceramics - Pimpilai Wannasut (2018)
© 2016 Taylor & Francis Group, LLC. Ternary system of lead-free piezoelectric ceramics with the formula of (1-x-y)Bi0.5(Na0.80K0.20)0.5TiO3-xLiNbO3-yBaTiO3or (1-x-y)BNKT-xLN-yBT (x = 0.005 and y = 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06 and 0.07 mol fraction) were sintered at the temperature of 1125°C for 2 h. All samples have the density ranging of 5.59 - 5.73 g/cm3. X-ray diffraction pattern exhibited a single perovskite structure without any secondary phase. Scanning electron micrographs indicated a cubic-like grain shape occurred for all compositions with side length of 0.49 - 0.77 μm. At a composition BNKT-0.005LN-0.04BT showed the highest piezoelectric coefficient (d33= 198 pC/N) with good dielectric (ϵr= 1775, tanδ = 0.0534) and ferroelectric properties (Pr= 17.36 μC/cm2, Rsq= 1.67).